2021
DOI: 10.3390/ma14143769
|View full text |Cite
|
Sign up to set email alerts
|

Study on Properties of Bone Glue/Polyurethane Composite Modified Asphalt and Its Mixture

Abstract: Composite modification technology is widely used in the materials field. To enhance the property of polyurethane modified asphalt and realize its application in road engineering, the bone glue/polyurethane composite modified asphalt (CMA) was prepared using bone glue, polyurethane, and neat asphalt in this research. The bone glue content ranges 5–10%, that of the polyurethane is 1–5%. The relationship between the modifier’s content and the conventional properties and rheological properties of CMA was revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…In order to investigate the changes in the rheological properties of asphalt under actual ambient temperature conditions, this study examined the changes in the rheological properties of asphalt materials using DSR according to the ASTM D7175 (AASHTO T31509) specification [25][26][27]. The oscillatory stress applied by this method better corresponds to the load conditions that asphalt experiences during actual service, thus providing a more accurate characterization of the asphalt's real-world performance.…”
Section: Dsr Testmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to investigate the changes in the rheological properties of asphalt under actual ambient temperature conditions, this study examined the changes in the rheological properties of asphalt materials using DSR according to the ASTM D7175 (AASHTO T31509) specification [25][26][27]. The oscillatory stress applied by this method better corresponds to the load conditions that asphalt experiences during actual service, thus providing a more accurate characterization of the asphalt's real-world performance.…”
Section: Dsr Testmentioning
confidence: 99%
“…A special network structure, more stable than those formed by other modifiers and asphalt, is formed by the chemical reaction between polyurethane and asphalt. This enhanced stability effectively improves the storage stability of asphalt and ensures that the performance of modified asphalt remains favorable over the long term [15]. Furthermore, studies conducted by respected scholars have demonstrated that incorporating polyurethane into asphalt leads to significant improvements in resistance against high-temperature rutting, aging, and water damage, as well as various other benefits.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…At present, animal bone glue is widely used in the industry, medical treatment, and other fields, and the application has been effective. , For example, Yan et al studied the bone glue/polyurethane composite modified asphalt (CMA) prepared using bone glue, polyurethane, and neat asphalt, and realized its application in road engineering . Norton et al studied the properties of bone adhesive and found that the chemical composition of bone adhesive can react in humid environments, forming a strong and durable bond with live bone and metal implants.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has exposed some defects such as easily cracking at low temperature and easily softening and flow at high temperature, which greatly limit the scope of its application [ 3 , 4 ]. In order to further promote the serviceability performance of asphalt, researchers have put forward a variety of improvement measures through unremitting efforts [ 5 , 6 , 7 , 8 , 9 ]. Among the many measures, the modification of asphalt using waste rubber powder was the most promising.…”
Section: Introductionmentioning
confidence: 99%